Corporate Entrepreneurship and International Performance: a Cross-Country Study - Hoeltgebaum, Dra., Marianne; Andreassi, Tales; Amal, Mohamed; Andersson, Svante; Hensbergen, Marleen (Revista de Negócios, 2018)
The overall purpose of this article is to examine the theoretical connections between Corporate Entrepreneurship-CE and International Performance-IP. More specifically, we address two main research questions: (1) How do different dimensions of CE influence IP and (2) To what extent the context of host country matters? Using a two-case study approach, we employ hybrid qualitativeâ€“quantitative analyses to address the effects of different dimensions of CE on IP. We adopted four statistical techniques: descriptive statistics, decision tree, cluster analysis, and principal components (factorial maps). The results show that country matters for the perception of the relationship between CE and IP. They show that it is meaningful to separate the different dimensions of CE (innovative behavior, new business ventures, competitive aggressiveness, product/service and process innovation, self-renewal,Â proactiveness, and risk taking) when examining their influence on IP. The paper focuses on three level of the organization: the production sector (staff), middle management (managers), and top management (CEO and directors). Such perspective allows to explore the role of first-level managers in a â€œbottom-upâ€ process of corporate entrepreneurship.Â  Furthermore, we distinguished between two levels of corporate entrepreneurship: results and entrepreneurial behavior.